Getting too old for this: Economic effects of ageing population in Finland - Mauri Kotamäki; Jonne Lehtimäki (Aboa Centre for Economics (ACE), 2024)
This paper investigates the impact of population ageing on the economic and fiscal performance of Finland, a small open economy, which has undergone a rapid and significant demographic shift since 2010. By employing the Synthetic Control Method (SCM) to create a counterfactual scenario without ageing while also controlling for a major part of structural changes in the industrial and business environments, we find that in 2019, Finland's real GDP per capita would have been 15.9% to 27.5% higher, productivity 8.4% to 13.9% higher, and general government debt 26.0 to 28.4 percentage points lower. Our findings are further validated by an instrumental variable approach, which supports the SCM results.
Keywords: E6; E61; E62; E65; J1; 330; Macroeconomic Policy; Macroeconomic Aspects of Public Finance; Fiscal Policy; Studies of Particular Policy Episodes; Demographic Economics